The future potential of Annona muricata L. extract and its bioactive compounds as radiation sensitizing agent: proposed mechanisms based on a systematic review - David Andi Wijaya; Melva Louisa; Heri Wibowo; Aslim Taslim; Tiara Bunga Mayang Permata; Handoko Handoko; Endang Nuryadi; Henry Kodrat; Soehartati Argadikoesoema Gondhowiardjo (Shahrekord University of Medical Sciences, 2021)
Despite technological advances in cancer treatment, especially in radiotherapy, many efforts are being made in improving cancer cell radio-sensitivity to increase therapeutic ratio and overcome cancer cell radio-resistance. In the present review, we evaluated the anticancer mechanism of Annona muricata L. (AM) leaves extract and its bioactive compounds such as annonaceous acetogenins, annomuricin, annonacin, or curcumin; and further correlated them with the potential of the mechanism to increase or to reduce cancer cells radio-sensitivity based on literature investigation. We see that AM has a promising future potential as a radio-sensitizer agent.